2020
DOI: 10.3389/fcell.2020.00734
|View full text |Cite
|
Sign up to set email alerts
|

Wnt Signaling Pathway Dysregulation in the Aging Brain: Lessons From the Octodon degus

Abstract: Wnt signaling constitutes a fundamental cellular and molecular pathway, necessary from proper embryogenesis to function-maintenance of fully developed complex organisms. In this regard, Wnt pathway plays a crucial role in both the development of the central nervous system and in maintaining the structure and function of the neuronal circuits, and it has been suggested that its dysregulation is critical in the onset of several pathologies including cancer and neurodegenerative disorders, such as Alzheimer’s dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 63 publications
1
19
0
Order By: Relevance
“…Based on the foregoing, appearance of agitation and the related changes in WNT5A DNA methylation could arise independently of peripheral inflammation so it will be necessary to examine the influence of neuroinflammation in future studies. Wnt signaling plays an important role in embryogenesis and is involved in the differentiation and development of the central nervous system [ 46, 47 ]. Further, Wnt signaling molecules are much expressed in the adult brain including the hippocampus and are involved in synapse maintenance and function [ 48 ] as well as in dopaminergic neuron formation and nerve regeneration [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Based on the foregoing, appearance of agitation and the related changes in WNT5A DNA methylation could arise independently of peripheral inflammation so it will be necessary to examine the influence of neuroinflammation in future studies. Wnt signaling plays an important role in embryogenesis and is involved in the differentiation and development of the central nervous system [ 46, 47 ]. Further, Wnt signaling molecules are much expressed in the adult brain including the hippocampus and are involved in synapse maintenance and function [ 48 ] as well as in dopaminergic neuron formation and nerve regeneration [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…The deficiency of SHH signaling in hypothalamus astrocytes prevents high-fat diet-induced obesity and insulin resistance, suggesting that astrocytic SHH signaling is a pivotal regulator in metabolic alterations associated with aging ( Tirou et al, 2021 ). A study in the Octodon degus demonstrated that Wnt signaling activity is decreased in the brain during aging ( Inestrosa et al, 2020 ). Notably, administration of ANDRO, an activator of the Wnt signaling, rescued the Wnt signaling loss in the brain of adult O. degus ( Inestrosa et al, 2020 ).…”
Section: Primary Cilia and Ciliary Signaling In Aging And Age-related...mentioning
confidence: 99%
“…Studies have further revealed that Wnt ligands (Wnt-2b, Wnt-6 and Wnt-7a), as well as frizzled receptors (Fzd-2 and Fzd-3), are downregulated in the aged human brain [ 44 ]. A study conducted by Inestrosa et al [ 45 ] revealed that soluble endogenous inhibitors of the Wnt signalling pathway increase in an age-dependent manner in both the hippocampus and cortex of Octodon degus . In addition, they reported that age-related Wnt signalling defects were recovered by andrographolide treatment in O. degus [ 45 ].…”
Section: Developmental Signalling Pathways and Ageing Brainmentioning
confidence: 99%
“…A study conducted by Inestrosa et al [ 45 ] revealed that soluble endogenous inhibitors of the Wnt signalling pathway increase in an age-dependent manner in both the hippocampus and cortex of Octodon degus . In addition, they reported that age-related Wnt signalling defects were recovered by andrographolide treatment in O. degus [ 45 ].…”
Section: Developmental Signalling Pathways and Ageing Brainmentioning
confidence: 99%